Público escolar no Museu de Ciências Morfológicas da UFMG: uma investigação acerca dessa experiência informacional - Patricia Carla Oliveira Carneiro (2018)
This research is inserted in the field of studies of information users and sought to understand the informational experience of students of basic education who visit the exhibitions of the Museum of Morphological Sciences of the Federal University of Minas Gerais (MCM / UFMG), at the initiative of their school. The research aims to approach the informational experience of students as a phenomenon that lies between the expectations of the teachers who proposed the visit, the specificities of the educational practice in the museums, and the agendas / interests / goals of the education professionals of these institutions. Inaugurated in 1997, the Museum of Morphological Sciences aims to provide the public with the contact with the human body and its study, to arouse interest in the search for new concepts on health and human life, as well as demonstrate the importance of preserving it, with quality. Many science museums seek to present innovative educational proposals with their own objectives in relation to what to teach and how to teach the subjects to which they dedicate themselves. But often, visits to these spaces are seen as a complementary resource to the activities developed in the classroom, which indicates that the relationship between the museum and the school may imply different expectations for each part. The theoretical model adopted in this study is Symbolic Interactionism, associated to the Clinical Information Approach; and the research method is the case study. Of qualitative nature, this research was developed in three stages: 1) exploratory period, which aimed to provide, through visits to the Museum, our entry into the field and the identification of data sources; 2) focused research, which consisted of systematic data collection through direct observation, semi-structured interview and semi-structured interview in focus group, and 3) analysis and interpretation of the data collected and the writing of the doctoral thesis. It is assumed that the meaning of the informational experience of visiting the MCM for students of basic education is not restricted to the reception of information illustrative of the contents developed in the classroom, covering unanticipated meanings. The data from this research indicate that this activity has repercussions in more subjective fields, which go beyond the objective contact with the scientific fact, evidencing the integration between science, the "I" and daily life.